Uroczysta procesja ku czci Najśw. Serca P. Jezusa. (Sopot : [s.n.], 1947)
Afisz inf. o procesji 15.06.1947 r.
Keywords: Wronka, Andrzej -- (1897-1974).; Gdańsk (Polska) -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- życie religijne; Wrzeszcz (Gdańsk, Polska ; dzielnica) -- 1945-1970 -- druki ulotne